Active inversion tectonics, simple shear folding and back-thrusting at Rioni Basin, Georgia. (March 2017) - Tibaldi, A.; Alania, V.; Bonali, F.L.; Enukidze, O.; Tsereteli, N.; Kvavadze, N.; Varazanashvili, O.
Abstract: The Rioni Basin, located between the Greater and Lesser Caucasus in Georgia, is an outstanding example of ongoing inversion tectonics. Marine and continental deposits of Cretaceous-Neogene age have been locally uplifted since the end of Miocene. The uplifted area totals 1300 km 2, and Plio-Quaternary river deposits have been raised up to 200 m above the surrounding plains. Inversion tectonics has been accompanied by the development of south-vergent asymmetrical folds and strike-slip faults along the border of the uplifted area. The folds have locally an en-échelon geometry and microtectonic data indicate rotation of the paleostress direction over time, suggesting simple shear deformation. In the interiors of the uplifted area, there are gentle symmetrical folds and one main active south-dipping reverse fault, corresponding to a backthrust. Morphostructural evidence, as well as the tilting of Quaternary strata, the offset of Quaternary alluvial deposits and the presence of crustal seismic activity, indicate that compressional tectonics is still active. The combination of field data with seismic reflection sections shows that inversion tectonics took place through a series of north-dipping blind thrusts and a wedge with passive back-thrusting. Uplift and contraction are more developed along the eastern part of the study area, suggesting the westward propagation of the closure of the Transcaucasian depression. Highlights: The Rioni Basin is an outstanding example of ongoing inversion tectonics. Structure, geomorphology, seismic reflection and seismicity show active tectonics. South-vergent folds, en-échelon folds, reverse and strike-slip faults developed. Main active north-dipping reverse faults and a backthrust have been recognized. Data suggest westward propagation of the closure of the Transcaucasian depression.